Antibacterial and anti-hyperlipidemic activities of the brown alga Hormophysa cuneiformis from Ad Dammam Seashore - Neveen Abdel-Raouf, Nouf Mohammad Al-Enazi, Ibraheem B.M. Ibraheem, Reem Mohammad Al-Harbie (Journal of Applied Pharmaceutical Science, 2015)
A laboratory experiment was conducted to test antibacterial activity of ethanol extract of the brown alga Hormophysa cuneiformis against three types of Gram- positive and three of Gram-negative bacteria, where extracts of this alga proved efficient activity against these pathogenic bacteria species ranged between medium and high suppression action. Also, we evaluated the effects of H. cuneiformis ethanolic extract and its major constituents on the serum lipid and protein levels of hyperlipidemic rats induced by the administration of a high-cholesterol diet. Results revealed the efficiency of H. cuneiformis extract in the decreasing the levels of the total cholesterol (TC), triglycerides (TG), low-density lipoproteins (LDL-C), blood urea nitrogen (BUN) and creatinine caused by alcohol. On the other hand, the treatment by alga extract exhibit significant increase in the high-density lipoproteins (HDL-C) (beneficial), total protein, albumin and globulins. The algal treatments also masking the lethal effects caused by harmful alcohol from raising the rate of enzymes ALT, AST, which returned to normal state in the groups treated by alga extract. Also, the histopathological examination of the ethanol treated groups of rate revealed degeneration and necrotic changes as compared to the administrated rate groups with alga extract which showed marked amelioration of the severity of these changes.
Keywords: Antibacterial activity, antioxidant activity, Hormophysa cuneiformis.